A stochastic geometric approach to coverage and connectivity in wireless sensor networks: cooperation and mobility. (8th November 2013) - Gao, Qinghai; Zou, Huilan
Depending on the density of a wireless sensor network, it is likely that the field is not completely covered and the network is not fully connected. Assuming that the sensor nodes are randomly deployed in the field, we observe that clumps of sensors could be formulated and cooperation among the sensor nodes can be carried out. With cooperation, the area covered by the sensor nodes increases and the data collected by each sensor could be shared within one clump. Moreover, mobile nodes (Mules) could be employed in the field to further improve the coverage and connectivity. In this paper, we characterise the expected proportion of covered region, the time needed to obtain full connectivity, and the number of nodes connected by the Mules at certain time threshold. Our analysis and simulation results show that significant improvement of coverage and connectivity can be achieved from cooperation and mobility.